Implementation Of Law Number 6 Of 2014 On Villages And Its Implications In Portibi Jae Village, North Padang Lawas Regency - Alamsyah; Khalid (Journal Equity of Law and Governance, 2025)
The aim of this research is to understand the implementation of Law No. 6 of 2014 on Villages and its implications for village development in Portibi Jae Village, Portibi District, North Padang Lawas Regency. Villages play a key role in the development of infrastructure and human resources (HR) in the region. The progress of a village impacts the development of the surrounding area and supports national development. This study is an empirical legal research that is descriptive and qualitative, using a case approach. The data collection techniques used are observation, interviews, and documentation. The results of the study show that the implementation of the Village Law in Portibi Jae Village has been carried out in accordance with applicable regulations, involving community participation, village governance, community economic empowerment, village fund management, and strengthening village institutions. The implications of the Village Law in Portibi Jae Village cover three main sectors: increased community participation, strengthened community economy through various programs including BUMdes (Village-Owned Enterprises), and improved village governance that is more accountable, transparent, and proactive, involving the village community. The impact of this implementation is reflected in the improvement of the physical condition of Portibi Jae Village, better village services, increased values of mutual cooperation in development, and the emergence of handcraft industries such as making bags and mats from gebang palm, mango syrup production, and banana chips by community groups. These activities contribute to the improvement of the community’s economy.